A normal - hidden markov model model in forecasting stock index - Tuyên, Lục Trí; Hùng, Nguyễn Văn; Ninh, Thạch Thị; Vương, Phạm Quốc; Đức, Nguyễn Minh; Kỳ, Đào Xuân (Journal of Computer Science and Cybernetics, 2012)
Stock market analysis and prediction are one of the interesting areas in which past data could be used to anticipate and predict data and information about the future. Technically speaking, this area is of high importance for professionals in the industry of finance and stock exchange as they can lead and direct future trends or manage crises over time. In this paper, we try to take advantage of Hidden Markov Models to analyze, model and predict the required data having the past data.